2023
DOI: 10.1021/jacs.3c00634
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Molecular Chirality Associated with Ferroelectric Switching in a High-Temperature Two-Dimensional Perovskite Ferroelectric

Abstract: Controlling molecular chirality by external stimuli is of great significance in both fundamental research and technological applications. Herein, we report a high-temperature (384 K) molecular ferroelectric of a Cu(II) complex whose spontaneous polarization can be switched associated with flipping of molecular chirality. In this two-dimensional perovskite structure, the inorganic layer is separated by (NH3(CH2)2SS(CH2)2NH3)2+ organic cations skewed in a chiral conformation (P- or M-helicity in an individual cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…The other study reports that one HOLHC based on achiral cystamine can undergo a phase transition corresponding to achiral packing and chiral packing . Very recently, another related study also observed similar phenomenon in hybrid organic copper chloride compounds based on the same organic cation derived from cystamine …”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The other study reports that one HOLHC based on achiral cystamine can undergo a phase transition corresponding to achiral packing and chiral packing . Very recently, another related study also observed similar phenomenon in hybrid organic copper chloride compounds based on the same organic cation derived from cystamine …”
Section: Resultsmentioning
confidence: 65%
“…27 Very recently, another related study also observed similar phenomenon in hybrid organic copper chloride compounds based on the same organic cation derived from cystamine. 28 Although the intramolecular hydrogen-bonding has a strong impact on the dimensionality reduction, it is noteworthy that other factors can also influence the structure. As mentioned in the Introduction, a series of aromatic-oxygen-alkyl-ammonium cations have been investigated, and they are all found to form 2D structures, although similar intramolecular hydrogen bonds are observed between ammonium groups and the O atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although all these examples involve a linear transition state, the oxygen BAI and nitrogen BAIs are distinct in the numbers of valence electron, bonding characters with ligands, and thus re-hybridization processes of central atoms (sp 3 -sp-sp 3 (O) vs. sp 2sp-sp 2 (N)). To date, there are no progresses in identifying the isomerization mechanism for bicoordinated O or its valence isoelectronic atoms (e.g., S in disulfide 12,13 ) or ions (e.g., N -) in the systems with conjugated M1-X-M2. Centered with N -, the anion bis(trifluoromethyl-sulfonyl)imide (TFSI -) is assumed to be conjugated among -SO2-N --SO2-.…”
Section: Introductionmentioning
confidence: 99%
“…1−8 In comparison with the traditional inorganic ferroelectrics, such as BaTiO 3 (BTO) and Pb(Zr,Ti)O 3 (PZT), molecular species offer the merits of mechanical flexibility, environmental friendliness, and transparent appearance. In recent years, numerous molecular ferroelectrics with diverse structures have been developed, and several intriguing ferroelectric-related phenomena have been observed, 9−17 including ferroelectric switching corresponding to the rotation of molecular rotors, 18−21 substantial piezoelectricity, 22−26 self-driven broad-spectrum polarized photodetection, 27,28 polarization switching associated with chiral inversion, 29 and simultaneous variation of electric ordering and magnetic properties. 30−35 For technological applications, a high operational temperature and a large P s are preferred.…”
mentioning
confidence: 99%
“…Molecular ferroelectrics, which exhibit a spontaneous polarization ( P s ) capable of being switched by an external electric field, have emerged as an exciting research frontier in materials science because of their great potential applications in nonvolatile memories, sensors, actuation, electro-optic devices, and others. In comparison with the traditional inorganic ferroelectrics, such as BaTiO 3 (BTO) and Pb­(Zr,Ti)­O 3 (PZT), molecular species offer the merits of mechanical flexibility, environmental friendliness, and transparent appearance. In recent years, numerous molecular ferroelectrics with diverse structures have been developed, and several intriguing ferroelectric-related phenomena have been observed, including ferroelectric switching corresponding to the rotation of molecular rotors, substantial piezoelectricity, self-driven broad-spectrum polarized photodetection, , polarization switching associated with chiral inversion, and simultaneous variation of electric ordering and magnetic properties. For technological applications, a high operational temperature and a large P s are preferred. However, metal-free molecular ferroelectrics that meet these requirements remain rare.…”
mentioning
confidence: 99%